(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Valued not only for its nutritional value or gastronomical pleasure, food, its preparation and its consumption have been an important marker of human culture and its evolution. Food practices are shaped by geo-cultural practices, social rules and hierarchies, influx of other food cultures and its ethnic core. To a great extent, an individual/community’s identity is shaped by what they consume. Food becomes a cultural reservoir through which a community or in individual can relate to past while being conscious of its absorption of other systems over time. Arundhati Roy’s The God of Small Things tells the story of the troubled childhood and adulthood of the twins Rahel and Estha in the backdrop of Kerala in 1960s and 1970s. She shows how the ethnic culture of Kerala transforms through the arrival of Western religion and culture, British colonization, cosmopolitanism and globalization, and is affected by dislocation, fragmentation and hybridity. Food becomes a functional metaphor for this cultural journey that blends the East with the West, modernity with ethnicity, and the individual with the community. The present paper focusses upon how culinary art works as a cultural component and a marker of the evolution of culture. It also aims to trace how it becomes a component of individual identity and how it helps an individual to reconnect with his/her past(s) and to redefine his/her ethnicity.